ASSESSMENT OF IMPLANTABLE PHAKIC CONTACT LENS OUTCOMES IN PATIENTS WITH HIGH MYOPIA: RELATIONSHIP BETWEEN CENTRAL VAULT AND INTRAOCULAR PRESSURE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: High Myopia Is A Significant Refractive Error Associated With Visual Impairment And Reduced Quality Of Life. Implantable Phakic Contact Lens (Ipcl) Implantation Has Emerged As A Safe And Effective Alternative For The Correction Of High Myopia, Particularly In Patients Unsuitable For Corneal Refractive Procedures. This Study Aimed To Evaluate The Clinical Outcomes Of Ipcl Implantation And Assess The Correlation Between Postoperative Central Vault And Intraocular Pressure (Iop). Methodology: A Prospective Observational Study Was Conducted In The Department Of Ophthalmology, Sree Mookambika Institute Of Medical Sciences, Kulasekharam, From October 2025 To February 2026. Fifty Eyes Of Patients Aged 21–50 Years With High Myopia (> -6.00 D) Underwent Ipcl Implantation. Preoperative And Postoperative Assessments Included Best Corrected Visual Acuity (Bcva), Spherical Equivalent (Mse), Intraocular Pressure, Anterior Chamber Parameters, And Vault Measurements Using Anterior Segment Optical Coherence Tomography. Follow-Up Examinations Were Performed On Postoperative Days 1, 7, And 30. Results: Postoperative Visual Acuity Improved Significantly, With 52% Of Eyes Achieving Bcva Of 6/6 At One Month Compared To 16% Preoperatively. Mean Spherical Equivalent Improved From -13.27 ± 4.26 D Preoperatively To -0.83 D Postoperatively. Mean Preoperative Iop Was 13.62 ± 2.69 Mmhg, Increasing To 16.08 ± 4.23 Mmhg At One Month. The Mean Postoperative Vault Was 706.42 Μm. A Significant Positive Correlation Was Observed Between Vault And Spherical Equivalent (P